(3QSGdI aj GdUhajIs - (3OGhhO Hf eMehO GdbjUQjs
(3ChdgG (B:s
(3bGd SjOfG eMeO Hf Ydi GdMeO ddg GdPi Ndb GdEfSGf Ydi UhQJg hNUg HSQjQJg CeG HYO aEf Gddg SHMGfg deG YQafi MbGFb GdCTjGA s
(3BNQgG (B:s
(3heGgi Ydjg HhLhO GdCchGf aJMbb gPG GdaUd GdeNJUQ GdYLjH aEfg fGaY ai GdHGH hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI eMeO CMeO GdeMGei (B_ (3GdHUQI (B(219 (3N(B) s
Keywords: (3GdeLGejYs